Bezugspunkte : 38-88. (Graz : Steirischer Herbst, 1988)
Daems, Walter ; Kogler + Scheffknecht ; Gerz, Jochen ; Fontana, Bill ; Haacke, Hans ; Sturm, Heribert ; Passow, Beate ; Dimitrijevic, Braco ; Ertl, Fedo ; Charlier, Jacques ; Hattan, Eric ; Gruppe Irwin ; Adams, Dennis ; Radermacher, Norbert ; Hofmeister, Werner ; Baren, Peter
Bezugspunkte 38-88, Graz Innenstadt, Steirischer Herbst '88, Graz, 15. Oktober - 8. November 1988
boek